WE WORK UNDER THE SIGN OF HRYHORII SKOVORODA : HISTORY AND DEVELOPMENT OF THE FACULTY OF PRIMARY EDUCATION - Довженко, Т.; Тихонович, В. (New Collegium, 2020)
The article describes the history of the Faculty of Primary Education of H.S. Skovoroda Kharkiv National Pedagogical University. information is given about the development of the Faculty structure, famous scholars and staff who worked at the faculty in different years. Basic directions of activity from the origins of the faculty to the present day are characterized.